PHONOLOGICAL ADAPTATION IN THE PROCESS OF BORROWING - Ruziev Khusniddin Bakhritdinovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article examines phonological adaptation of foreign words in English. It highlights changes in vowels, consonants, stress, and syllable structure. Examples from French, Italian, and Spanish show how borrowed words are made pronounceable and integrated into English.